Mobility and associations with levels of cerebrospinal fluid amyloid β and tau in a memory clinic cohort - Tangen, Gro Gujord; Sverdrup, Karen; Taraldsen, Kristin; Persson, Karin; Engedal, Knut; Bekkhus-Wetterberg, Peter; Knapskog, Anne-Brita (Frontiers in Aging Neuroscience, 2023)
Background Mobility impairments, in terms of gait and balance, are common in persons with dementia. To explore this relationship further, we examined the associations between mobility and cerebrospinal fluid (CSF) core biomarkers for Alzheimer’s disease (AD). Methods In this cross-sectional study, we included 64 participants [two with subjective cognitive decline (SCD), 13 with mild cognitive impairment (MCI) and 49 with dementia] from a memory clinic. Mobility was examined using gait speed, Mini-Balance Evaluation Systems test (Mini-BESTest), Timed Up and Go (TUG), and TUG dual-task cost (TUG DTC). The CSF biomarkers included were amyloid-β 42 (Aβ42), total-tau (t-tau), and phospho tau (p-tau181). Associations between mobility and biomarkers were analyzed through correlations and multiple linear regression analyses adjusted for (1) age, sex, and comorbidity, and (2) SCD/MCI vs. dementia. Results Aβ42 was significantly correlated with each of the mobility outcomes. In the adjusted multiple regression analyses, Aβ42 was significantly associated with Mini-BESTest and TUG in the fully adjusted model and with TUG DTC in step 1 of the adjusted model (adjusting for age, sex, and comorbidity). T-tau was only associated with TUG DTC in step 1 of the adjusted model. P-tau181 was not associated with any of the mobility outcomes in any of the analyses. Conclusion Better performance on mobility outcomes were associated with higher levels of CSF Aβ42. The association was strongest between Aβ42 and Mini-BESTest, suggesting that dynamic balance might be closely related with AD-specific pathology.